Bird ringing and nest recording in Britain and Ireland in 2015. Issue 2 (1st December 2016) - Walker, Ruth H.; Robinson, Robert A.; Leech, Dave I.; Moss, Dorian; Barimore, Carl J.; Blackburn, Jeremy R.; Barber, Lee J.; Clewley, Gary D.; de Palacio, Diana X.; Grantham, Mark J.; Griffin, Bridget M.; Kew, Allison J.; et al.
ABSTRACT: This is the 79 th annual report of the British Trust for Ornithology's Ringing Scheme, incorporating the report of the Nest Record Scheme and covering work carried out and data processed in 2015. Constant Effort Sites (CES) data from across Europe, relating to eight common warblers, were analysed to investigate large-scale variation in survival rates and showed that changes in survival outside the breeding season are not a key driver of long-term population trends. Retrapping Adults for Survival (RAS) seabird data sets were reviewed to understand their ability to supplement geographically limited, long-term studies carried out by professionals. Most RAS studies re-encountered sufficient numbers of seabirds to estimate average survival rates; however, only those with re-encounter rates of around 40% were able to detect changes in survival rates efficiently. Over 100, 000 nest records, relating to four insectivorous woodland passerines, were used to investigate changes in laying dates in response to temperature. Laying dates advanced by 2.3–4.8 days per °C rise in temperature, suggesting that these species may be able to change their laying dates in response to climate changes, even if the rate of climate change is rapid. Over 10, 000 phenological data sets, including laying dates for 37 bird species, were used to look at the mechanisms behind species' responses to changes in climate. Primary producers and primary consumers advanced timing of breeding more quickly than secondary consumers, potentially leading to a greater mismatch between the timing of breeding in birds (secondary consumers) and their prey availability under future climate-change projections. Data were received for 134 CE sites in 2015. Long-term (1984–2014) population trends derived from the CES data identified five migrant species and four resident species that have decreased significantly in abundance over this period. Abundance of three species decreased significantly in 2015 compared to the five-year mean (2010–14) with Whitethroat Sylvia communis abundance at its lowest since CES monitoring began. There were significant increases in abundance for 12 species, with Goldfinch Carduelis carduelis at its highest since CES monitoring began. Productivity decreased significantly in ten species and increased significantly in three species compared to the five-year mean (2010–14); productivity for Willow Warbler Phylloscopus trochilus was at its lowest since CES began. There were no significant changes in survival in 2015. The total number of active RAS projects increased again in 2015; 190 submissions were received, including data from 23 new projects. Projects were carried out on 57 species, with Pied Flycatcher Ficedula hypoleuca (23 projects), Sand Martin Riparia riparia (15) and House Sparrow Passer domesticus (20) still the most-studied species. The total number of birds ringed in 2015 was just under one million (987, 253) and comprised 472, 462 first-year birds, 319, 230 adults (birds in their second calendar year or older), 27, 993 unaged birds and 167, 568 nestlings. In addition, there were 236, 540 recaptures of ringed birds at or near the ringing site. In total, 32, 253 recoveries (birds found dead, or recaptured or resighted at least 5 km from the place of ringing) of BTO-ringed birds were reported in 2015. A selection of recoveries that have extended our knowledge of movements is presented, as well as longevity records established during the year. In total, 48, 957 nest records were received for 2015, the highest annual submission since the Scheme began in 1939. Mean laying dates for five species were significantly earlier than the five-year mean (2010–14) with nine species laying significantly later. Only one species showed a significant increase in breeding success (fledglings per breeding attempt) in 2015, with four decreasing significantly. A total of 612 permits/licences to disturb breeding birds on Schedule 1 of the Wildlife and Countryside Act 1981 (as amended), were prepared/issued in 2015, a small increase from 2014. During 2015, the use of special methods was authorised for 489 marking projects and 68 trapping projects, 25% more than in 2014.